2023
DOI: 10.1002/cjoc.202200785
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous α‐Diimine Nickel Catalysts with Improved Catalytic Performance in Ethylene Polymerization

Abstract: More importantly, the structure and properties of the polymer products can be controlled by catalyst structures, polymerization conditions and heterogenization to achieve good mechanical properties and elasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…These trends are similar to those reported in the literatures. 49,53 Heterogeneous pre-catalysts Ni1@SiO 2 and Ni2@SiO 2 can catalyze ethylene polymerization under the same polymerization conditions as their homogeneous simulants Ni1 and Ni2 (Table 2, entries 1-5), resulting in high activities (up to 3.5 Â 10 6 g mol À1 h À1 ) and high molecular weights (up to 67 kg mol À1 ). It was shown that the positions of the anchoring groups have significant effects on catalytic performances.…”
Section: Ethylene Homo-polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These trends are similar to those reported in the literatures. 49,53 Heterogeneous pre-catalysts Ni1@SiO 2 and Ni2@SiO 2 can catalyze ethylene polymerization under the same polymerization conditions as their homogeneous simulants Ni1 and Ni2 (Table 2, entries 1-5), resulting in high activities (up to 3.5 Â 10 6 g mol À1 h À1 ) and high molecular weights (up to 67 kg mol À1 ). It was shown that the positions of the anchoring groups have significant effects on catalytic performances.…”
Section: Ethylene Homo-polymerizationmentioning
confidence: 99%
“…Interestingly, some recent reports show that heterogenization effect may significantly improve the catalytic performances of various nickel-based olefin polymerization catalysts (Chart 1a,H-K). 3,22,[46][47][48][49] This is due to the influences of heterogenization on the steric hindrance and electronic effects of the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of polar functional groups can significantly enhance the compatibility of polyolefins with polar components, thereby contributing to the preparation of high‐performance composites both in the melt blending process and in the in situ polymerization route [3–7, 31–33] . However, the typical heterogenization route remains largely unexplored in late transition metal olefin polymerization catalyst systems [7, 34–41] . In order to achieve high polymerization activity and universal applicability to different fillers, it is often necessary to synthesize new catalysts bearing specific anchoring groups (Figure 1C, right) [7, 34–43] .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][31][32][33] However, the typical heterogenization route remains largely unexplored in late transition metal olefin polymerization catalyst systems. [7,[34][35][36][37][38][39][40][41] In order to achieve high polymerization activity and universal applicability to different fillers, it is often necessary to synthesize new catalysts bearing specific anchoring groups (Figure 1C, right). [7,[34][35][36][37][38][39][40][41][42][43] Furthermore, catalyst performances may be significantly altered due to the interaction of the support with the catalyst at the molecular level, resulting in poor predictability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation